Crude Nutrient and Mineral Composition of Asystasia gangetica (L.) as a Predominant Forage Species for Feeding of Goats - Khalil (Pakistan Journal of Nutrition, 2016)
The present study was aimed to define the suitability of Asystasia gangetica (L.) as a predominant forage for goats based on crude nutrient and mineral composition. Samples of forages collected by farmers were taken from 8 goat farms at three different sampling times. Fresh samples were taken from five different spots in each sample bunch from each farm, weighed and then sorted to determine the predominant species based on botanical composition and apparent frequency. Samples of six predominant species were chopped and mixed in with others from the same sampling time. Representative samples (about 150 g) from each of the predominant species were dried and ground for chemical analysis. Botanical composition, apparent frequency, dry matter, nutrient content (crude protein, fiber and ash) and minerals (Ca, P, Fe, Cu, Mn and Zn) were measured. Results showed that of the 47 total kinds of vegetation fed to goats in the Payakumbuh region of Indonesia, the six predominant forage species included Axonopus compressus (23.4%), Centrocema pubescens (6.8%), A. gangetica (5.5%), Panicum maximum (5.3%) and Gliricidia sepium (5.2%) and Manihot utilissima (5.0%) foliage. The crude nutrient and mineral content of A. gangetica showed it to be a good source of protein and minerals, particularly Ca, P, Cu, Mn and Zn. It was concluded that A. gangetica could be used as a good complementary source of protein and minerals for goats.